Mapping Global Research Output in Big Data during 2007-16 - S.M. Dhawan; Brij Mohan Gupta; Ritu Gupta (Emerging Science Journal, 2018)
The paper examines global research in big data, as covered in Scopus database 2007-16, on a series of bibliometric indicators. The study finds that big data registered exceedingly fast growth (135.2%), but averaged low citation impact per paper (3.75) and accounted for very low share of highly cited papers (0.86%) in 10 years. The study reports publication trends in big data research by top countries, top institutions, top authors, top journals, major subject areas, publication modes, and country-level share of international collaborative publications. The study concludes that big data is a subject of recent origin. Given its major potential to impact business, governance, society, healthcare, industry and many other sectors, big data is fast emerging as a major discipline of interest and importance to nations, corporates, and institutions across developed and fast emerging economies.